2014
DOI: 10.1371/journal.pone.0106416
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated with Implementation of Computer-Assisted Clinical Decision Support System for Antenatal and Delivery Care: Case Study of Kassena-Nankana District of Northern Ghana

Abstract: ObjectiveThis study analyzed cost of implementing computer-assisted Clinical Decision Support System (CDSS) in selected health care centres in Ghana.MethodsA descriptive cross sectional study was conducted in the Kassena-Nankana district (KND). CDSS was deployed in selected health centres in KND as an intervention to manage patients attending antenatal clinics and the labour ward. The CDSS users were mainly nurses who were trained. Activities and associated costs involved in the implementation of CDSS (pre-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Electronic tools may support the focus on evidence-based medicine, and the QUALMAT project could show that health care personnel are waiting for health IT. Challenges to implement such a system may be overcome, and the costs may be justifiable [Sukums F personal communication, Saronga HP personal communication, and ( 26 , 42 )]. However, the study presented here showed both expected and unexpected results and added to what was previously known in this area ( 2 , 3 , 17 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electronic tools may support the focus on evidence-based medicine, and the QUALMAT project could show that health care personnel are waiting for health IT. Challenges to implement such a system may be overcome, and the costs may be justifiable [Sukums F personal communication, Saronga HP personal communication, and ( 26 , 42 )]. However, the study presented here showed both expected and unexpected results and added to what was previously known in this area ( 2 , 3 , 17 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of personnel turnover (some personnel transferred to other health facilities or went for studies) subsequent training was necessary. Training has been found to take up substantial resources in other CDSS interventions as well [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mishandled deployment and narrow capabilities of MHWs can cause increases in costs of home visits up to twice that of clinical visits [7]. Fortunately, cost of implementation, laptops and computers buying expenses, can be balanced with reduction of operation costs long-term [5,6].…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…Edit An Existing Referral (6) Record Notes About A Visit (7) Send A Reminder To A Client (8) Send An Article to A Client (9) Review Client's Article Viewing History (10) Add A Reminder for Yourself …”
Section: Task Descriptionmentioning
confidence: 99%